2021
DOI: 10.3389/fpsyg.2021.731279
|View full text |Cite
|
Sign up to set email alerts
|

Service Quality in Tourism Public Health: Trust, Satisfaction, and Loyalty

Abstract: The spread of COVID-19 and large-scale travel restrictions has caused serious damage to the global tourism industry. Tourists pay additional attention to public health services and their health during travel, but studies on tourism public health service quality (TPHSQ) are limited. Therefore, this study aims to define TPHSQ and revise and validate its scale. The result of exploratory factor analysis (EFA) indicates that TPHSQ includes two dimensions “overall environmental image” and “public health facilities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 51 publications
1
32
0
6
Order By: Relevance
“…For example, Ling and Ding (2006) found that increasing customer satisfaction was effective in promoting customer loyalty, which gave firms an advantage in survival and competition. Han et al (2021) also found that satisfaction had a positive and significant effect on loyalty. Similar findings are now available in the field of education.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…For example, Ling and Ding (2006) found that increasing customer satisfaction was effective in promoting customer loyalty, which gave firms an advantage in survival and competition. Han et al (2021) also found that satisfaction had a positive and significant effect on loyalty. Similar findings are now available in the field of education.…”
Section: Introductionmentioning
confidence: 85%
“…This means that the more satisfied parents are, the more likely they are to keep their children in school. Previous empirical studies have found that satisfaction has a significant and positive effect on loyalty ( Cabello-Manrique et al, 2021 ; Han et al, 2021 ; Río-Rama et al, 2021 ). Budiyanto et al (2021) showed that parental satisfaction had a significant and positive effect on parental loyalty.…”
Section: Literature Reviewmentioning
confidence: 96%
See 1 more Smart Citation
“…With this premise, Armstrong et al (1997) later expanded the concept of service into the five dimensions of service quality that comprised tangibles, reliability, responsiveness, assurance, and empathy. Extant literature on service delivery focuses on the traditional emphasis on the contact between the customer and service provider (Mechinda and Patterson, 2011;Han et al, 2021). Doucet (2004) explained that the quality in these traditional settings depends on the design of the location and the behavior of the service provider.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Extant literature on service delivery focuses on the traditional emphasis on the contact between the customer and service provider ( Mechinda and Patterson, 2011 ; Han et al, 2021 ). Doucet (2004) explained that the quality in these traditional settings depends on the design of the location and the behavior of the service provider.…”
Section: Literature Reviewmentioning
confidence: 99%